Sex-dependent effects of an early life treatment in rats that increases maternal care: vulnerability or resilience? - Fuentes, Silvia; Daviu, Núria; Garrido, Pedro; Gagliano, Humberto; Zelena, Dóra; Monasterio, Nela; Armario, Antonio; Nadal, Roser (Frontiers in Behavioral Neuroscience, 2014)
Early life stress (ELS) in rodents has profound long-term effects that are partially mediated by changes in maternal care. ELS not only induces “detrimental” effects in adulthood, increasing psychopathology, but also promotes resilience to further stressors. In Long-Evans rats, we evaluated a combination of two procedures as a model of ELS: restriction of bedding during the first postnatal days and exposure to a “substitute” mother. The maternal care of biological and “substitute” mothers was measured. The male and female offspring were evaluated during adulthood in several contexts. Anxiety was measured by the elevated plus-maze (EPM), acoustic startle response (ASR) and forced swim test (FST). In other group of animals, novelty-seeking was measured (activity in an inescapable novel environment, preference for novel environments and exploration of novel objects). Plasmatic ACTH and corticosterone in basal conditions and in response to stress were also measured. Cognitive impulsivity was assessed by a delay-discounting paradigm, and impulsive action, attention and compulsive-like behaviour by a five choice serial reaction time task (5CSRTT). ELS decreased pup body weight and increased the care of the biological mother; however, the “substitute” mother did not exhibit overt maltreatment. A mixture of “detrimental” and “beneficial” effects was shown. In the 5CSRTT, attention was impaired in both genders, and in females, ELS increased compulsive-like behaviour. Novel object exploration was only increased by ELS in males, but the preference for novel spaces decreased in both genders. Baseline anxiety (EPM and ASR) and recognition memory were not affected. Unexpectedly, ELS decreased the ACTH response to novelty and swim stress and increased active coping in the FST in both genders. Cognitive impulsivity was decreased only in females, but impulsive action was not affected. The enhancement in maternal care may “buffer” the effects of ELS in a context-dependent manner.